Outcomes from the medication assisted treatment pilot program for adults with opioid use disorders in rural Colorado - Claudia R. Amura; Tanya R. Sorrell; Mary Weber; Andrea Alvarez; Nancy Beste; Ursula Hollins; Paul F. Cook (BMC, 2022)
Abstract Background As Colorado ranked among the top nationally in non-medical use of opioids, a pilot medication for opioid use disorder (MOUD) program was developed to increase the number of NPs and PAs providing MOUD in order to bring this evidence- based treatment to 2 counties showing disproportionally high opioid overdose deaths. Over the first 18 months, the MOUD Pilot Program led to 15 new health care providers receiving MOUD waiver training and 1005 patients receiving MOUD from the 3 participating organizations. Here we evaluate patient centered clinical and functional outcomes of the pilot MOUD program implemented in 2 rural counties severely affected by the opioid crisis. Methods Under state-funded law (Colorado Senate Bill 17-074), three rural agencies submitted de-identified patient-level data at baseline (N = 1005) and after 6 months of treatment (N = 190, 25%) between December 2017 and January 2020. The Addiction Severity Index, PhQ9 and GAD-7 with McNemar-Bowker, and Wilcoxon Signed Rank tests analysis were used to measure patient outcomes across after participation in the program. . Results Patients in treatment reported using less heroin (52.1% vs 20.4%), opioids (22.3% vs 11.0%), and alcohol (28.6% vs 13.1%, all P < 0.01). Patients reported improved health (53.4% vs. 68.2%, P = 0.04), less frequency of disability (8.69 vs. 6.51, P = 0.02), symptoms (29.8% vs 21.3%), pain (67.5% to 53.6), worry (45.3% vs 62.3%), anxiety (49.7% vs 23.2%), depression (54.1% vs 23.3%, all P < 0.02) after treatment. Conclusions This study shows decreased substance use, improved physical and mental health, and reduced symptoms after 6 months of MOUD. Although more research on retention and long-term effects is needed, data shows improved health outcomes after 6 months of MOUD. Lessons learned from implementing this pilot program informed program expansion into other rural areas in need to address some of Colorado' major public health crises.